PENGARUH PENGETAHUAN, KETERAMPILAN DAN SIKAP KERJA TERHADAP KINERJA PENGELOLA BADAN USAHA MILIK DESA (BUMDES) DIKECAMATAN PALIBELO - Komang Sika; Hermanto Hermanto; Agus Susanto (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Village-Owned Enterprises (BUMDes) are village business entities that are managed by residents and village governments in an effort to strengthen the village economy and build socio-economic residents based on the needs and abilities of the village. oriented towards improving economic and social welfare, functioning actively in an effort to improve the quality of human life and citizens, strengthening the people's economy as under the strength and resilience of the economy. (BUMDes) in Palibelo District. This research is an associative research, namely research that seeks a relationship between one variable and another. The relationship used is a causal relationship that is causal. In this type of research, there are hypotheses that will be tested for truth. The hypothesis itself describes the relationship between two or more variables and to find out whether a variable is associated or not with other variables, and or whether a variable is caused/influenced or not by other variables. The research sample of all BUMDes members of Palibelo District was 54 people. The research instrument is a questionnaire using a Likert scale. The data is then analyzed using multiple linear regression analysis. The results show that knowledge, attitudes and work skills have a significant and positive influence on the performance of BUMDes managers in Palibelo District, Bima Regency. Village governments throughout the Palibelo sub-district should pay more attention to the performance of BUMDes managers by recruiting managers based on competence and carrying out strict supervision of the performance of managers so that the results of supervision become the basis for evaluating the work of each manager.